Peripheral and central arterial pressure and its relationship to vascular target organ damage in carotid artery, retina and arterial stiffness. Development and validation of a tool. The Vaso risk study - Garcia-Ortiz, Luis (BioMed Central, 2011)
BACKGROUND: Ambulatory blood pressure monitoring (ABPM) shows a better correlation to target organ damage and cardiovascular morbidity-mortality than office blood pressure. A loss of arterial elasticity and an increase in carotid artery intima-media thickness (IMT) has been associated with increased cardiovascular morbidity-mortality. Tools have been developed that allow estimation of the retinal arteriovenous index but not all studies coincide and there are contradictory results in relation to the evolution of the arteriosclerotic lesions and the caliber of the retinal vessels. The purpose of this study is to analyze the relationship between peripheral and central arterial pressure (clinic and ambulatory) and vascular structure and function as evaluated by the carotid artery intima-media thickness, retina arteriovenous index, pulse wave velocity (PWV) and ankle-brachial index in patients with and without type 2 diabetes. In turn, software is developed and validated for measuring retinal vessel thickness and automatically estimating the arteriovenous index. METHODS/DESIGN: A cross-sectional study involving a control group will be made, with a posterior 4-year follow-up period in primary care. The study patients will be type 2 diabetics, with a control group of non-diabetic individuals. Consecutive sampling will be used to include 300 patients between 34-75 years of age and no previous cardiovascular disease, one-half being assigned to each group. Main measurements: age, gender, height, weight and abdominal circumference. Lipids, creatinine, microalbuminuria, blood glucose, HbA1c, blood insulin, high sensitivity C-reactive protein and endothelial dysfunction markers. Clinic and ambulatory blood pressure monitoring. Carotid ultrasound to evaluate IMT, and retinography to evaluate the arteriovenous index. ECG to assess left ventricle hypertrophy, ankle-brachial index, and pulse wave analysis (PWA) and pulse wave velocity (PWV) with the Sphigmocor System. DISCUSSION: We hope to obtain information on the correlation of different ABPM-derived parameters and PWA to organ target damage - particularly vascular structure and function evaluated from the IMT and PWV - and endothelial dysfunction in patients with and without type 2 diabetes. We also hope to demonstrate the usefulness of the instrument developed for the automated evaluation of retinal vascularization in the early detection of alterations in vascular structure and function and in the prognosis of middle-term cardiovascular morbidity. TRIAL REGISTRATION: Clinical Trials.gov Identifier: NCT01325064